Children can discriminate the authenticity of happy but not sad or fearful facial expressions, and use an immature intensity-only strategy - Dawel, Amy; Palermo, Romina; O’Kearney, Richard; McKone, Elinor (Frontiers in Psychology, 2015)
Much is known about development of the ability to label facial expressions of emotion (e.g., as happy or sad), but rather less is known about the emergence of more complex emotional face processing skills. The present study investigates one such advanced skill: the ability to tell if someone is genuinely feeling an emotion or just pretending (i.e., authenticity discrimination). Previous studies have shown that children can discriminate authenticity of happy faces, using expression intensity of the happy expressions as an important cue, but have not tested the negative emotions of sadness or fear. Here, children aged 8-12 years (n = 85) and adults (n = 57) viewed pairs of faces in which one face showed a genuinely-felt emotional expression (happy, sad, or scared) and the other face showed a pretend version. For happy faces, children discriminated authenticity above chance, although they performed more poorly than adults. For sad faces, for which our pretend and genuine images were equal in intensity, adults could discriminate authenticity, but children could not. Neither age group could discriminate authenticity of the fear faces. Results also showed that children judged authenticity based on intensity information alone for all three expressions tested, while adults used a combination of intensity and other factor/s. In addition, novel results show that individual differences in empathy (both cognitive and affective) correlated with authenticity discrimination for happy faces in adults, but not children. Overall, our results indicate late maturity of skills needed to accurately determine the authenticity of emotions from facial information alone, and raise questions about how this might affect social interactions in late childhood and the teenage years.